Application of the S-procedure in multiple comparisons for nonlinear models - Shim, Kyu Bark (Edelweiss Applied Science and Technology, 2024)
Zerbe (1979) characterized the growth curve model as one of the nonlinear models. For these models, we propose a comprehensive procedure to identify significant differences in multiple comparisons of fully randomized growth curve models. Research applying Scheffé’s S-procedure to growth curve models as a subclass of nonlinear models has yet to be conducted. Our findings demonstrate that the S-procedure is an effective method for discerning important differences within a fully randomized growth curve model.